Development of a Geotourism-Based Learning Model to Improve Geography Understanding and Environmental Awareness of Secondary School Students - Junaidin; Munandar (Journal of Social Studies Education, 2025)
This research aims to develop a geotourism-based learning model to enhance students’ understanding of geography concepts and environmental awareness at MAN 1 Bima. The study arose from the low ability of students to connect geographical concepts with real environmental phenomena. The research employed a qualitative approach with a model development design. Participants consisted of 50 individuals, including 45 grade XI social science students and 5 geography teachers. Data were collected through observation, in-depth interviews, and document analysis, then analyzed using Miles and Huberman’s interactive model. The findings revealed that the developed model consists of three main components: field exploration, conceptual reflection, and conservation action. The model effectively increased student engagement, spatial understanding, and environmental awareness, particularly regarding local natural tourism management and disaster mitigation. Therefore, the geotourism-based learning model is recommended as a pedagogical innovation for geography education at the secondary school level.